Frank McKinney’s maverick approach to real estate success : - McKinney, Frank (John Wiley & Sons, 2006)
Frank McKinney, is certainly a maverick and a spiritually grounded young man. The oceanfront homes he builds here in Florida are magnificent and unique. More important, Frank's life and the contributions he makes to his community and the world illustrate how a successful businessman can do well while doing good. The principles in Frank McKinney's Maverick Approach to Real Estate Success represent a road map of his achievements--a proven strategy for succeeding not just in real estate, but also in the business of life.